Prevalence and factors associated with intestinal parasites among food handlers of food and drinking establishments in Aksum Town, Northern Ethiopia - Dejen Gezehegn; Mebrahtu Abay; Desalegn Tetemke; Hiwet Zelalem; Hafte Teklay; Zeray Baraki; Girmay Medhin (BMC, 2017)
Abstract Background Various epidemiological studies indicate that the prevalence of intestinal parasites is high in developing countries and those parasites are major public health importance in Sub-Saharan Africa. Their distribution is mainly associated with poor personal hygiene, environmental sanitation and lack of access to clean water. This study was conducted to estimate the prevalence of intestinal parasitic infection and identify factors associated with intestinal parasitic infection among food handlers in the Aksum Town of Tigray Regional State, North Ethiopia. Methods A cross-sectional study design was used among 400 randomly selected food handlers who were selected as respondents. Data were collected by face to face interviewer administered questionnaire supplemented with observational checklist. Fresh stool samples were collected from respondents and were examined microscopically for the presence of any of intestinal parasites using standard laboratory methods. Multivariable logistic regression model using Adjusted Odds Ratio (AOR) and 95% Confidence Interval (CI) was fitted to analyze the independent predictors of intestinal parasitic infections. Result The mean age of the food handlers included in this study was 26.0 years. Of the total respondents, 72.5% were females, 63% have completed at least secondary school educational level. Five species of Intestinal Parasites (IPs) were identified. The overall prevalence of being infected with at least one intestinal parasite was 14.5%, 95% CI (11.3, 18.0). The odds of being positive for at least one intestinal parasitic infection was 12.3 times higher among food handlers who practice medical checkup every 9 months compared to those who have a medical checkup every 3 months. The odds of being positive for intestinal parasitic infection was 3 times higher among food handlers with no formal education compared to those who have a level of education secondary school and above. Food handlers who received food hygiene and safety training were 66% less likely to be positive for at least one intestinal parasitic infection as compared to those who did not receive training. Conclusion Prevalence of parasitic infection among food handlers observed in the current study is relatively low but is still a public health importance. Number of medical checkup, training in food hygiene and safety, feedback from customers and level of education were significantly associated with reduced odds of being infected with parasitic infection. Hence, these factors should be focused by policy makers and implementers to further bring the prevalence below the level of public health importance.